2012
DOI: 10.4017/gt.2012.11.02.355.00
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian model for real-time safety management in construction sites

Abstract: Purpose This article reports on an ongoing research project, which is aimed at implementing advanced probabilistic models for real-time identification of hazardous events at construction sites. The model has intelligent capabilities for near real-time automated recognition of hazardous events during the execution phase. To achieve this, features of Bayesian Networks have been exploited. In addition, inputs to the model are assumed to be provided by a pervasive monitoring system deployed on the site. The need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The 'Pathfinder project' by Heckerman et al (1992), that used BN expert system to diagnose medical condition of patients, has reported successful use of BN in performing critical analysis in many complex situations. Argiolas et al (2012); Hossain and Muromachi (2012) reported use of BN for safety related accident prediction applications. Early detection of leakages in boilers using BN has also been reported by Widarsson and Dotzauer (2008).…”
Section: Introductionmentioning
confidence: 98%
“…The 'Pathfinder project' by Heckerman et al (1992), that used BN expert system to diagnose medical condition of patients, has reported successful use of BN in performing critical analysis in many complex situations. Argiolas et al (2012); Hossain and Muromachi (2012) reported use of BN for safety related accident prediction applications. Early detection of leakages in boilers using BN has also been reported by Widarsson and Dotzauer (2008).…”
Section: Introductionmentioning
confidence: 98%